One hundred days : the memoirs of the Falklands battle group commander - Woodward, Sandy; Robinson, Patrick, 1939- (Annapolis, Md. : Naval Institute Press, 1992)
The day they hit HMS Sheffield -- The submariner -- Argentina invades -- South to Ascension -- "Weapons tight!"--The final approach -- 1 May : the war begins -- The bells of hell -- The silence of HMS Sheffield -- The end of the trail for Narwal -- Glasgow's bomb -- Atlantic rendezvous -- Night landing -- The battle of "Bomb Alley"--Calamity for Coventry -- The marines will have to walk -- Port unpleasant -- Welcome home -- Epilogue.
The day they hit HMS Sheffield -- The submariner -- Argentina invades -- South to Ascension -- "Weapons tight!" -- The final approach -- 1 May : the war begins -- The bells of hell -- The silence of HMS Sheffield -- The end of the trail for Narwal -- Glasgow's bomb -- Atlantic rendezvous -- Night landing -- The battle of "Bomb Alley" -- Calamity for Coventry -- The marines will have to walk -- Port unpleasant -- Welcome home -- Epilogue.
Includes index.
Keywords: Woodward, Sandy; Woodward, Sandy; Great Britain. -- Royal Navy -- History -- Falkland Islands War, 1982.; Great Britain. -- Royal Navy; 1982; Falkland Islands War, 1982 -- Personal narratives, British; Personal Narrative; Personal narratives; History; Personal narratives -- British; Personal narratives; 2